Changes in orogenic style and surface environment recorded in Paleoproterozoic foreland successions - Huang, B.; Liu, M.; Kusky, T.M.; Johnson, Tim; Wilde, Simon; Fu, D.; Deng, H.; Qian, Q. (2023)
The Earth’s interior and surficial systems underwent dramatic changes during the Paleoproterozoic, but the interaction between them remains poorly understood. Rocks deposited in orogenic foreland basins retain a record of the near surface to deep crustal processes that operate during subduction to collision and provide information on the interaction between plate tectonics and surface responses through time. Here, we document the depositional-to-deformational life cycle of a Paleoproterozoic foreland succession from the North China Craton. The succession was deposited in a foreland basin following ca. 2.50–2.47 Ga Altaid-style arc–microcontinent collision, and then converted to a fold-and-thrust belt at ca. 2.0–1.8 Ga due to Himalayan-style continent–continent collision. These two periods correspond to the assembly of supercratons in the late Archean and of the Paleoproterozoic supercontinent Columbia, respectively, which suggests that similar basins may have been common at the periphery of other cratons. The multiple stages of orogenesis and accompanying tectonic denudation and silicate weathering, as recorded by orogenic foreland basins, likely contributed to substantial changes in the hydrosphere, atmosphere, and biosphere known to have occurred during the Paleoproterozoic.